What are the Experts Saying About Business Marketing Communication Applications in the Digital Age? - B.M.A.S. Anaconda Bangkara; Rainier Hendrik Sitaniapessy; Irma Rachmawati Maruf; Endang Fatmawati; Yuli Purbaningsih (Institute of Computer Science (IOCS), 2022)
This study aims to understand what experts say in business marketing communication applications in the era. The search for data has been successful; we have provided technical assistance on several data that we believe are relevant to the problem, namely the marketing communication application business. We examine the data under a phenomenological approach to gain understanding from several existing data so that the data is valid in answering the problem. Based on the study and discussion, it is explained that several applications can be used in marketing business products in this era of digital applications. In essence, the application is a very communicative marketing model that connects business people with customers online. It is hoped that these findings will be helpful in the development of further studies in both academic and industrial contexts.